Generation of anti-inflammatory adenosine by leukocytes is regulated by TGF-β. - Regateiro, F; Howie, D; Nolan, K; Agorogiannis, E; Greaves, D; Cobbold, S; Waldmann, H (2011)
Levels of anti-inflammatory extracellular adenosine are controlled by the sequential action of the ectonucleotidases CD39 and CD73, whose expression in CD4(+) T cells has been associated with natural regulatory T cells (nTregs). We here show that CD73 expression on activated murine CD4(+) T cells is induced by TGF-β independently of Foxp3 expression, operates at the transcriptional level and translates into gain of functional capacity to generate adenosine. In the presence of AMP, CD73 induced by TGF-β generates adenosine able to suppress proliferation of activated CD4(+) T cells in vitro. These effects are contextual and opposed by proinflammatory cytokines. CD73 is also upregulated by TGF-β in CD8(+) T cells, DCs and macrophages, so providing an amplification mechanism for adenosine generation in tissue microenvironments. Together, these findings expose a novel anti-inflammatory role for TGF-β.